Sistem Informasi Donor Darah Menggunakan Barcode pada Rumah Sakit Umum Liunkendage Tahuna - Steven M.F. Banduge; Ella H. Israel; Oktavianus Lumasuge (Jurnal Ilmiah Tindalung, 2015)
The hospital is one of the public sector organizations engaged in health services for the community, one of which langanan form of blood donors at the blood transfusion unit. But in the service units of blood transfusion services in particular blood donor experience many obstacles, which delay the handlers of the patient, because the system is still in use in data processing manually donor, so that the service that is given is inaccurate and not timely. This study aims to design and build a system of blood donors using barcode information that can help piece unit blood transfusion in a blood donor services. The system is built using Visual Basic 6.0, Microsoft Access 2007, the barcode scanner as a supporting component andcrystal report. The results of this study in which the system is able to process data in the donor blood donor services to perform the data input and the stock of blood donors and in the process into the system so as to present a report that is accurate and useful for blood donor services.